2019
DOI: 10.3390/antiox8040079
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Light-Induced Retinal Degeneration by Quercetin via the AP-1 Pathway in Rats

Abstract: We examined the cytoprotective effect of quercetin via activator protein (AP-1) and the heat shock protein 70 (Hsp70) pathway against light-induced retinal degeneration in rats. Quercetin was administered intraperitoneally to Sprague-Dawley rats for seven days before light exposure to intense white fluorescent light (3000 lux) for 24 h. Light-induced retinal damage was determined by the number of rows of photoreceptor cell nuclei, the microstructures of the rod outer segments and retinal pigment epithelium, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…(2010) in their different experiments observed that 50 μM of quercetin protected human RPE cells from oxidative stress, cellular senescence and also inhibited pro-inflammatory molecules, which resulted in the prevention of age-related macular degeneration (AMD). Koyama et al. (2019) reported that 50 mg/bodyweight/kg of quercetin in rat model experiment decreased photooxidative damage in the rat retina.…”
Section: Effects Of Dietary Natural Plant Products Against Age-relatementioning
confidence: 99%
See 1 more Smart Citation
“…(2010) in their different experiments observed that 50 μM of quercetin protected human RPE cells from oxidative stress, cellular senescence and also inhibited pro-inflammatory molecules, which resulted in the prevention of age-related macular degeneration (AMD). Koyama et al. (2019) reported that 50 mg/bodyweight/kg of quercetin in rat model experiment decreased photooxidative damage in the rat retina.…”
Section: Effects Of Dietary Natural Plant Products Against Age-relatementioning
confidence: 99%
“… Inhibits age-related eye diseases. Koyama et al. (2019) Quercetin 50 mg/kg/day Diabetic rat retina Protects the neuronal damage, ameliorates neurotrophic factors and inhibits the apoptosis of neurons Prevents neurodegeneration in diabetic retinopathy.…”
Section: Protective Effects Of Dietary Natural Plant Products Againstmentioning
confidence: 99%
“…In a different model of peroxide-induced oxidative stress model in RPE cells [409] quercetin treatment influenced the transcription of genes involved in apoptosis regulation, including the anti-apoptotic Bcl-2 and the proapoptotic BAX and FADD, and the effectors of apoptosis Caspase-3 and Caspase-9. Intraperitoneal administration of quercetin blunted the photo-oxidative damage of rat retinas' photoreceptors exposed to intense light [410]. Curcumin, a polyphenol from Curcuma longa (turmeric plant) belonging to the ginger family, is also able to modulate apoptosis, inflammation and oxidative stress defense proteins [411]; these effects follow the upregulation of the anti-apoptotic protein Bcl-2, the downregulation of the pro-inflammatory transcription factor NF-kB, and the upregulation of the antioxidant proteins SOD, GR and HO-1, as shown in human retinal cell models exposed to oxidative damage [350,412].…”
Section: Polyphenolsmentioning
confidence: 94%
“…On the other hand, some studies have demonstrated that quercetin has an inhibitory effect of heat shock protein 72 (HSP 72) in RGCs [ 95 , 96 , 97 ]. Quercetin has neuroprotective effects of retinal layers [ 98 ] and cytoprotective effects of photoreceptor, RPE and RGCs through inhibiting activity of AP-1 pathway [ 99 ] in light-induced retinal degeneration rodent models. It attenuates hyperglycemia [ 100 ] and dyslipidemia [ 101 ], and also has anti-retinal oxidative stress, anti-neuroinflammation and anti-apoptosis protective effects in diabetic animal models [ 102 ].…”
Section: Neuroprotective Effects Of Nutraceuticals In Animal Studimentioning
confidence: 99%